2012
DOI: 10.1155/2012/193923
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Mechanisms Involved in the Control of Tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) infection is a major international public health problem. One-third of the world's population is thought to have latent tuberculosis, a condition where individuals are infected by the intracellular bacteria without active disease but are at risk for reactivation, if their immune system fails. Here, we discuss the role of nonspecific inflammatory responses mediated by cytokines and chemokines induced by interaction of innate receptors expressed in macrophages and dendritic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 196 publications
(218 reference statements)
3
133
0
Order By: Relevance
“…Several studies indicate that circulating immune cells are activated and recruited to the M. tuberculosis-infected lungs to form the granuloma where the M. tuberculosis proliferation is controlled by an active interaction of lymphocytes and infected macrophages [15][16][17][18][19][20]. In a previous study, we observed that peripheral white blood cell (WBC) subpopulation ratios varied according to TB clinical status in a limited number of BCG-vaccinated individuals from an area with a high TB burden [17].…”
Section: Introductionmentioning
confidence: 92%
“…Several studies indicate that circulating immune cells are activated and recruited to the M. tuberculosis-infected lungs to form the granuloma where the M. tuberculosis proliferation is controlled by an active interaction of lymphocytes and infected macrophages [15][16][17][18][19][20]. In a previous study, we observed that peripheral white blood cell (WBC) subpopulation ratios varied according to TB clinical status in a limited number of BCG-vaccinated individuals from an area with a high TB burden [17].…”
Section: Introductionmentioning
confidence: 92%
“…9,10 Antigen-specific CTL activity is known to play an essential role in clearing these pathogens. To evaluate the impact of PLA microspheres on antigen-specific CTL activity, we performed 51 Cr release assays.…”
Section: Microsphere Vaccines Elicit Enhanced Ifn-γ Secretion and Spementioning
confidence: 99%
“…After fusion has occurred, the infected macrophages and dendritic cells may undergo apoptosis [37], trapping any surviving bacteria in the cell and leaving them vulnerable for further phagocytosis and internalization (and possibly infection) of other cells. Joller et al [38] reviewed the role of phagosome Fc receptors in enhancing the efficacy of fusion and killing intracellular pathogens [39].…”
Section: The Immune Response To Mtbmentioning
confidence: 99%